2020
DOI: 10.1101/2020.04.09.20056242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liver injury is associated with severe Coronavirus disease 2019 (COVID-19) infection: a systematic review and meta-analysis of retrospective studies

Abstract: Aim: The Coronavirus disease 2019 outbreak is a major threat to human beings.Lung injury has been reported as the major outcome of COVID-19 infection. However, liver damage has also been considered to occur in severe cases. Current meta-analysis of retrospective studies was done to summarize available findings on the association between liver injury and severity of COVID-19 infection.Methods: Online databases including PubMed, Scopus, Web of Science and Cochrane Library were searched to detect relevant public… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 53 publications
6
55
0
6
Order By: Relevance
“…We have also compared our results with previous meta‐analysis (Table 3). 4,5,119‐125 This is the first study to report the liver involvement of all adults, pregnant patients and paediatric patients with COVID‐19. We have analysed in‐depth about the liver involvement in COVID‐19, including elevated liver chemistries at initial presentation, during illness and the impact of this on the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We have also compared our results with previous meta‐analysis (Table 3). 4,5,119‐125 This is the first study to report the liver involvement of all adults, pregnant patients and paediatric patients with COVID‐19. We have analysed in‐depth about the liver involvement in COVID‐19, including elevated liver chemistries at initial presentation, during illness and the impact of this on the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Generally only ALT/AST levels were frequently reported, with scarce information on LDH, previous infections, glucose or CRP. These data were also missing in a recent meta-analysis by Parohan et al, who concluded that the incidence of liver injury may be higher in patients with severe COVID-19 infection [64]. Similarly Xu et al [11] summarized the reports of liver injury caused by SARS-CoV, MERS-CoV and SARS-CoV-but were unable to define the mechanisms of liver injury associated with SARS-CoV-2 infection.…”
Section: Covid-19 Patients and Liver Injurymentioning
confidence: 99%
“…[ 3 , 7 , 8 ] Previous meta-analyses also explored the association between gastrointestinal manifestations and the severity of COVID-19 infection. [ 9 11 ] But some results in these meta-analyses were inconsistent and the association between specific digestive symptoms, such as abdominal pain and constipation, and COVID-19 prognosis remains unclear. Furthermore, these meta-analyses drew conclusions based on limited sample sizes and almost all evidence from China.…”
Section: Introductionmentioning
confidence: 99%